Aerobic exercise modalities on gut microbiome and skeletal muscle quality in ovariectomized mice - Li, Tao; Lu, Yongjun; Yu, Fangfang; Zhong, Qiuling; Meng, Yifan; Feng, Yiwei; Hu, Yi; Tian, Xiangyang; Li, Tingting; Shi, Rengfei (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to investigate the effects of aerobic exercise on skeletal muscle quality, gut microbiota composition, and estrogen levels in ovariectomized (OVX) mice, and to elucidate the potential underlying mechanisms, thereby providing experimental evidence for exercise intervention in postmenopausal women.MethodsAdult female C57BL/6J mice were randomly assigned to four groups (n = 6 per group): Sham, OVX, Sham+ET, and OVX+ET. After 6 weeks of recovery, the exercise groups received 8 weeks of treadmill training. Muscle morphology, function, and protein metabolism pathways were assessed using histology, grip tests, and Western blotting. Aromatase and estrogen levels were evaluated by immunofluorescence and ELISA. Gut microbiota composition was analyzed via 16S rRNA sequencing and correlated with muscle function.ResultsEight weeks of aerobic exercise significantly improved skeletal muscle mass, fiber cross-sectional area, and grip strength in OVX mice, and reduced fatigue index compared to OVX controls. Immunofluorescence revealed increased aromatase expression and intramuscular E2 levels following exercise, with no significant difference in serum estradiol. Western blot analysis indicated activation of the Akt/mTOR/p-S6 pathway and inhibition of FOXO3-mediated protein degradation. 16S rRNA sequencing showed that exercise increased α-diversity (Shannon and Simpson indices) and altered microbial community structure, as shown by distinct clustering in PCoA plots. At the genus level, exercise modulated the relative abundance of several bacterial taxa. Spearman correlation analysis demonstrated that microbial diversity indices were positively associated with lean mass and fatigue resistance.ConclusionAerobic exercise significantly improves muscle mass and function in ovariectomized mice, potentially through a combined mechanism involving regulation of protein metabolism, enhancement of local estrogen synthesis, and modulation of gut microbiota composition.